Impacts of Cryopreservation on Semen Quality and Sperm Protein Profiles of Pesisir Bulls - Ananda; Gusdinal, H.; Ramadhan, R.; Abimanyu, A. A.; Ningsih, W. H.; Jaswandi (Tropical Animal Science Journal, 2025)
This study aimed to evaluate the impacts of cryopreservation on semen quality and sperm protein profile in Pesisir bulls. Semen samples were collected from three bulls and analyzed in fresh and post-thaw conditions. The sperm motility and kinematic variables were assessed using Computer-Assisted Sperm Analysis (CASA), while sperm viability and plasma membrane integrity (PMI) were evaluated through eosin-nigrosin staining and the hypoosmotic swelling test (HOST), respectively. Subsequently, the total protein concentration (PC) and profile were examined using SDS-PAGE. The results showed that there was a significant decrease in semen quality after thawing, with sperm motility reducing from 81.10% to 70.22%, viability reducing fom 87.47% to 77.27%, and PMI reducing from 85.09% to 71.32% (p<0.05). Kinematic variables such as velocity, straightness, and beat cross frequency also decreased significantly. Protein analysis showed a reduction in total concentration from 1.78 mg/mL to 1.19 mg/mL and alterations in protein band distribution, with the loss of specific high- and low-molecular weight after freezing. These results suggested that cryopreservation negatively impacts semen quality and sperm protein integrity, potentially impairing fertility. Moreover, further studies were recommended to optimize cryopreservation protocols and mitigate adverse effects.